A scheme to analyses the statements of the student in context of problem posing - Espinoza-González, Johan (2015)
The problem posing is considered as an important activity in the formation of mathematical skills of students, so they have made efforts to study it as a process of instruction in math classes; however, few investigations addressed strategies designed to assess student productions at this type of task. Thus, the construction and implementation of a analyses scheme that was used in a broader research study that aimed to characterize the arithmetic performance of a group of talented students in mathematics is presented. To do an analysis of the study variables of arithmetic problems and a study of the tools used in previous research was conducted, which allowed define three categories of analysis and in each study variables. The results show the feasibility of such a scheme to characterize the problems invented by students, identify different levels of complexity in the same and to assess the degree of profundity and appropriation of the knowledge learned.